ХАЛЫҚ ШАЙЫРЛАРЫ ПОЭЗИЯСЫНЫҢ КӨРКЕМ ДӘРЕКЛЕРИ - Оразымбетова, М.К. (FAN va JAMIYAT, 2017)
The article is devoted to the study of artistis sources in the poetry of people’s poets. There were analysed the folklore and oriental literary traditions in the works of the poets Abdikadir, Kulmurat, Ayapbergen and others.